BEROBAT DENGAN BENDA HARAM DALAM PERSPEKTIF ISLAM - Endri Yenti (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Technological developments not only change human lifestyles, but also affect human food patterns. At present it is difficult to get foods that are free of chemical substances, because many foods are served instantaneously, but the side effects they cause tend to be dangerous, because they can trigger various dangerous diseases such as cancer. Many patients who experience cancer or other dangerous diseases suffer by the poor, this causes them to seek treatment that is cheap and easy to find such as consuming various types of plants that are believed to cure. The tendency above raises the rampant offer of easy and inexpensive alternative medicine in the treatment is carried out with various methods such as herbal medicine with plants to extreme treatment by using unclean and consuming animals that are forbidden and unclean treatment. In principle, Islam strongly encourages its people to make medication efforts but still does not come out of halal principles. This is illustrated in several hadiths of the Prophet Muhammad who forbade medical treatment with objects that are forbidden such as the prohibition of the Prophet Muhammad to use Khamar as a medicine. In Shahih al-Bukhari it is stated that as soon as Allah SWT does not make healing from something that is forbidden.